Implikasi Kebebasan Pers Terhadap Dinamika Politik Islam di Sumatera Utara Pada Masa Reformasi Periode 1998-2011 - Nirwansyah Putra (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Post-reform period, press is not facing the power only, but also capital-media owner and professionalism itself. This impacted political Islam dynamics in North Sumatra, directly or indirectly. Islamic political discourse in the media during 1998-2011 period, inseparable with the political Islam depoliticization in the past as well as the power and economy pragmatism, also determines the general islamic discourse and weakening the potential political power of Islam. The absence of Islamic political media and structured-systematic special programs in Islamic journalism and the existence of media that are generally common-secular segmented, causing the agenda and the political Islam discourse depends on owner ideological considerations, market segmentation and policy of secular media.